(untitled) (Nigerian Journal of Technology, 2002)
This paper described the mathematical basis and computational framework of a computer program developed for short circuit studies of electric power systems. The Short Circuit Analysis Program (SCAP) is to be used to assess the composite effects of unbalanced and balanced faults on the overall reliability of electric power system. The program uses the symmetrical components method to compute all phase and sequence quantities for any bus or branch of a given power network resulting from the application of balanced and unbalanced faults at any location of the system. The Key to the efficient computer implementation of this program is the utilization of the triangular factorization of the positive and zero sequence admittance matrices, thus avoiding the time consuming direct formation of the sequence impedance matrices.